Economic Impact of Foot and Mouth Disease in Dairy Farmers at Koperasi Peternakan Bandung Selatan (KPBS) Pangalengan, Indonesia - Taufiqqurrahman, Mas; Sudarnika, Etih; Lukman, Denny Widaya (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
This study aims to analyze the economic impact of the foot and mouth disease (FMD) outbreak on dairy farmers who are members of the Pangalengan South Bandung Livestock Cooperative (KPBS). Data were collected through structured questionnaires, in-depth interviews, and field observations of 100 FMD-affected farmers during September-November 2023, with follow-up evaluation one year after the outbreak. The results showed that during the outbreak (29 days), the average loss per farmer reached IDR 44,018,068 or IDR 6,288,295 per head, mostly due to decreased milk production, dairy cow mortality, and disease control costs, including treatment, vaccination, and disinfection. One year after the outbreak (365 days), economic losses were IDR 46,077,090 or IDR 6,582,441 per head, dominated by the residual impact of FMD in the form of a 39.75% reduction in milk yield (18.31 kg/day). Economic losses also involved additional costs, such as vector control and livestock burial, which further burdened farmers. These findings highlight the importance of more effective FMD control policies, including mass vaccination, improved biosecurity and financial assistance for affected farmers, to reduce economic impacts and support long-term recovery.